Literature review on autonomous production control methods - Martins, Luis (2020)
Production environments are becoming more complex and dynamics. This is influenced by external factors related with products’ characteristics and costumers’ requirements and internal factors related with processing times variability, machine failures, setup times, between others. To face this increasing complexity and dynamics, it is crucial to have effective production control methods, considering Interoperability Enablers for Cyber-Physical Systems. However, production control methods most in used today, are focused on centralised decision-making and planning, and considered inadequate to deal with the increasing dynamics of these systems. Autonomous Production Control (APC) may be an adequate alternative to face this complexity, allowing flexible and rapid reaction to possible disturbances that may occur in the production system. However, as APC is the relatively new concept, there are no existing surveys. Therefore, we review and discuss the literature on APC methods to bring more attention to this promising topic of research, highlighting future research directions.